Modeling a Small Punch Testing Device - Habibi, S.; Ziadi, A.; Megueni, A. (Engineering, Technology & Applied Science Research, 2014)
A small punch test of a sample in miniature is implemented in order to estimate the ultimate load of CrMoV ductile steel. The objective of this study is to model the ultimate tensile strength and ultimate load indentation according to the geometrical parameters of the SPT using experimental data. A comparison of the model obtained with the two models (European code of practice and method of Norris and Parker) allows the design and dimensioning of an indentation device that meets the practical constraints. Implemented as a Matlab program, allows the investigation of new combinations of test variables.